Folate hydrolase‐1 (FOLH1) is a novel target for antibody‐based brachytherapy in Merkel cell carcinoma - M. K. Ramirez‐Fort; B. Meier‐Schiesser; K. Lachance; S. S. Mahase; C. D. Church; M. J. Niaz; H. Liu; V. Navarro; A. Nikolopoulou; D. V. Kazakov; E. Contassot; D. P. Nguyen; et al. (Wiley, 2021)
Abstract Backgrounds Folate Hydrolase‐1 (FOLH1; PSMA) is a type II transmembrane protein, luminally expressed by solid tumour neo‐vasculature. Monoclonal antibody (mAb), J591, is a vehicle for mAb‐based brachytherapy in FOLH1+ cancers. Brachytherapy is a form of radiotherapy that involves placing a radioactive material a short distance from the target tissue (e.g., on the skin or internally); brachytherapy is commonly accomplished with the use of catheters, needles, metal seeds and antibody or small peptide conjugates. Herein, FOLH1 expression in primary (p) and metastatic (m) Merkel cell carcinoma (MCC) is characterized to determine its targeting potential for J591‐brachytherapy. Materials & Methods Paraffin sections from pMCC and mMCC were evaluated by immunohistochemistry for FOLH1. Monte Carlo simulation was performed using the physical properties of conjugated radioisotope lutetium‐177. Kaplan-Meier survival curves were calculated based on patient outcome data and FOLH1 expression. Results Eighty‐one MCC tumours were evaluated. 67% (54/81) of all cases, 77% (24/31) pMCC and 60% (30/50) mMCC tumours were FOLH1+. Monte Carlo simulation showed highly localized ionizing tracks of electrons emitted from the targeted neo‐vessel. 42% (34/81) of patients with FOLH1+/− MCC had available survival data for analysis. No significant differences in our limited data set were detected based on FOLH1 status (p = 0.4718; p = 0.6470), staining intensity score (p = 0.6966; p = 0.9841) or by grouping staining intensity scores (− and + vs. ++, +++, +++) (p = 0.8022; p = 0.8496) for MCC‐specific survival or recurrence free survival, respectively. Conclusions We report the first evidence of prevalent FOLH1 expression within MCC‐associated neo‐vessels, in 60‐77% of patients in a large MCC cohort. Given this data, and the need for alternatives to immune therapies it is appropriate to explore the safety and efficacy of FOLH1‐targeted brachytherapy for MCC. What's already known about this topic? We report the first evidence of prevalent folate hydrolase‐1 (FOLH1; also known as prostate‐specific membrane antigen) expression within MCC‐associated neovessels. What does this study add? Herein, FOLH1 expression in Merkel cell carcinoma neovasculature is validated, and the therapeutic mechanism of specific, systemic targeting of disseminated disease with antibody‐based brachytherapy, is defined.